Identifikasi jenis layanan bimbingan konseling dalam upaya memberikan informasi kesehatan mental pada peserta didik - Tyas, Devi Marganing; Pertiwi, Anggun; Nisa, Vania Zaimatun (PSYCOMEDIA : Jurnal Psikologi, 2023)
This study aims to identify the types of counseling guidance services provided by the school to provide mental health information to students. The method used in this research is descriptive-qualitative. The informants in this study were three counseling guidance teachers. Data collection techniques in this study used the interview method. Test the validity of the data in this study using data triangulation techniques. The results showed that counseling guidance services carried out by schools consist of four basic components: basic services, individual services, responsive services, and system support services. The service areas that focus on mental health education are personal services and social services. Educational institutions need to collaborate with other partners, such as health workers and parental involvement to provide mental health information to students.